2022
DOI: 10.1021/acsinfecdis.2c00164
|View full text |Cite
|
Sign up to set email alerts
|

Cationic, Steroid-Based Imidazolium Amphiphiles Show Tunable Backbone-Dependent Membrane Selectivity in Fungi

Abstract: Cationic amphiphiles have been reported to show broad antimicrobial activity. The potential for antimicrobial resistance to these molecules is low owing to their general cell membrane permeabilizing mode of action. However, their applications are often limited by toxicity resulting from their low selectivity for microbial cell membranes. Herein, we report a library of cationic, steroid-based imidazolium amphiphiles that show tunable antifungal activity in a variety of fungal pathogens of the genus Candida. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…We recently introduced a novel class of imidazolium-based lipid analogs that exhibit an amphiphilic structure similar to natural lipids and allow flexible molecular tuning of their function and biological properties. 9 In particular, a series of cholesterol analogs (cholesterol-imidazoliums, CHIMs) were developed that were shown to faithfully mimic the properties of endogenous cholesterol and to enable tracking of cholesterol distributions and dynamics in live cells. 10 Their unique design permits the flexible attachment of a large variety of functional groups, such as a clickable azide moiety (CHIM-L), in the C2-position of the imidazolium ring which show a well-defined positioning at the outer membrane surface while at the same time preserving cholesterol's natural amphiphilic character.…”
Section: Introductionmentioning
confidence: 99%
“…We recently introduced a novel class of imidazolium-based lipid analogs that exhibit an amphiphilic structure similar to natural lipids and allow flexible molecular tuning of their function and biological properties. 9 In particular, a series of cholesterol analogs (cholesterol-imidazoliums, CHIMs) were developed that were shown to faithfully mimic the properties of endogenous cholesterol and to enable tracking of cholesterol distributions and dynamics in live cells. 10 Their unique design permits the flexible attachment of a large variety of functional groups, such as a clickable azide moiety (CHIM-L), in the C2-position of the imidazolium ring which show a well-defined positioning at the outer membrane surface while at the same time preserving cholesterol's natural amphiphilic character.…”
Section: Introductionmentioning
confidence: 99%
“…Moody group applied late-stage Chan-Lam amination to effective construction of diverse triazole-contained integrin inhibitors with various substituents for idiopathic pulmonary fibrosis (IPF) drug SAR study ( Scheme 29 b) 354 . Recently Glorius and Fridman developed steroid-based and ergosterol-based triazole cationic amphiphiles for antifungal bioactive compounds optimization ( Scheme 29 c) 355 . Furthermore, Moss and Wang found that the reduction of amyloid- β protein (A β ) plateau significantly increased about 2-fold when introduced tetrazole into the cyano position of the parent compound, which implied the newly introduced tetrazole structure might occupy an essential binding site ( Scheme 29 d) 356 .…”
Section: Nitrogenation Of Bioactive Compoundsmentioning
confidence: 99%